Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/s20010249
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Characterization of Femtosecond Laser-Inscribed Bragg Grating in Polymer Waveguide Operation in an IR-A Wavelength Range

Abstract: Optical sensors, such as fiber Bragg gratings, offer advantages compared to other sensors in many technological fields due to their outstanding characteristics. This sensor technology is currently transferred to polymer waveguides that provide the potential for cost-effective, easy, and flexible manufacturing of planar structures. While sensor production itself, in the majority of cases, is performed by means of phase mask technique, which is limited in terms of its degrees of freedom, other inscription techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The temperature sensitivity of the sensor is similar to the waveguide Bragg grating sensor presented by Meyer et al, who used the same photo resist for the fabrication of their non-evanescent sensors and achieved -44 pm/K temperature sensitivity. 5 The validation of the liquid-phase evanescent field of the RWBG sensor was carried out by applying different aqueous isopropyl (IPA)-water mixture ranging from 0-99.9% IPA concentration. During the measurements, According to the measurement results, the sensitivity of the RWBG sensor in the range of 1.33 to 1.38 refractive index unit (RIU) increases from 2.7 nm/RIU for pure water to 6.5 nm/RIU for 99.9% pure IPA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature sensitivity of the sensor is similar to the waveguide Bragg grating sensor presented by Meyer et al, who used the same photo resist for the fabrication of their non-evanescent sensors and achieved -44 pm/K temperature sensitivity. 5 The validation of the liquid-phase evanescent field of the RWBG sensor was carried out by applying different aqueous isopropyl (IPA)-water mixture ranging from 0-99.9% IPA concentration. During the measurements, According to the measurement results, the sensitivity of the RWBG sensor in the range of 1.33 to 1.38 refractive index unit (RIU) increases from 2.7 nm/RIU for pure water to 6.5 nm/RIU for 99.9% pure IPA.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Therefore, optical waveguides, manufactured without claddings, are better suited for evanescent sensing applications. Polymer planar waveguide optical sensors with Bragg grating structures were presents by Meyer et al 5 The presented sensor has shown an increased sensitivity compared to FBGs in temperature and strain. However, their presented sensor was coated with an additional cladding layer, shielding the environment from interaction with the evanescent field.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of fiber-based spectrometers with fiber Bragg gratings (FBG) are an enormously powerful approach to build more compact, more robust, and cost-effective sensors since the whole spectrometer consist only of the fiber with the dispersive and focusing FBG and a line sensor affixed to the FBG portion of the fiber [22,23]. The improved compactness is preferential also for robust applications in harsh and industrial environments.…”
Section: Chromatic Confocal Sensors (Ccs)mentioning
confidence: 99%
“…A fiber Bragg grating structure could be processed in the core of the fiber and were able to embed Fourier optics and non-diffractive beam devices on the end face of the fiber [38]. In addition, the Bragg grating was inscribed with a near-infrared femtosecond laser through point irradiation to modulate the refractive index of the material [39].…”
Section: Manufacturing and Applications Of Sensorsmentioning
confidence: 99%